Insightful understanding of three-phase interface behaviors in 1T-2H MoS2/CFP electrode for hydrogen evolution improvement - Cao, Jiamu; Zhou, Jing; Li, Mingxue; Chen, Junyu; Zhang, Yufeng; Liu, Xiaowei (Chinese chemical letters, 2022)
Hydrogen evolution reaction (HER) catalytic electrodes under actual working conditions show interesting mass transfer behaviors at solid (electrode)/liquid (electrolyte)/gas (hydrogen) three-phase interfaces. These behaviors are essential for forming a continuous and effective physical contact region between the electrolyte and the electrode and require further detailed understanding. Here, a case study on 1T-2H phase molybdenum disulfide (MoS2)/carbon fiber paper (CFP) catalytic electrodes is performed. Rapid gas-liquid mass transfer at the interface for enhancing the working area stability and capillarity for increasing the electrode working area is found. The real scenario, wherein the energy utilization efficiency of the as-prepared non-noble metal catalytic electrode exceeds that of the noble metal catalytic electrode, is disclosed. Specifically, a fluid dynamics model is developed to investigate the behavior mechanism of hydrogen bubbles from generation to desorption on the catalytic electrode surface with different hydrophilic and hydrophobic properties. These new insights and theoretical evidence on the non-negligible three-phase interface behaviors will identify opportunities and motivate future research in high-efficiency, stability, and low-cost HER catalytic electrode development. [Display omitted]